Stick Gymnastic Development for Learning Material Rhythmic Activities at Physical Education in Elementary Schools (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
This research aims to produce stick model gymnastics products, find out the effectiveness, and acceptability of students and physical education teachers. Borg & Gall's model development research procedures include: preliminary product analysis, expert validation, field trials, product revisions, and final product development results. The results of this research are stick exercise models in the form of DVDs and guidebooks. The research data contained a significant increase from field trials on psychomotor aspects from 10% to 34.6%. Affective from 23.3% to 45.2%. Cognitive from 53.3% to 67.3%. Conclusion Researchers have developed appropriate stick gymnastics as a learning media for elementary school students, effectively making students move actively, and can be accepted by students and physical education teachers.